Adapting to intersectoral transfers in the Zhanghe Irrigation System, China: Part I - In-system storage characteristics - Roost Nicolas; Xueliang Cai; David, S.; Yuanlai Cui (2008)
The Zhanghe Irrigation System (ZIS), in Central China, has drawn attention internationally because it managed to sustain its rice production in the face of a dramatic reallocation of water to cities, industries and hydropower uses. Ponds, the small reservoirs ubiquitous in the area, are hypothesized to have been instrumental in this. Ponds are recharged by a combination of return flows from irrigation and runoff from catchment areas within the irrigated perimeter. They provide a flexible, local source of irrigation water to farmers. This paper assesses the storage capacity and some key hydrological properties of ponds in a major canal command within ZIS. Using remote sensing data (Landsat and IKONOS) and an area-volume relationship based on a field survey, we obtained an overall pond storage capacity of 96 mm (per unit irrigated area). A comparative analysis between 1978 and 2001reveals that part of this capacity results from a very significant development of ponds (particularly in the smaller range of sizes) in the time interval, probably as a response to rapidly declining canal supplies. We developed a high-resolution digital elevation model from 1:10,000 topographic maps to support a GIS-based hydrological analysis. Pond catchments were delineated and found to extensively overlap, forming hydrological cascades of up to 15 units. In a 76-km2 area within the irrigation system, we found an average of close to five 'connected' ponds downstream of each irrigated pixel. This high level of connectivity provides opportunities for multiple reuses of water as it flows along toposequences. A fundamental implication is that field 'losses' such as seepage and percolation do not necessarily represent losses at a larger scale. Such scale effects need to be adequately taken into account to avoid making wrong assumptions about water-saving interventions in irrigation.